ANALYSIS OF THE EFFECTIVENESS OF SOCIAL MEDIA AS A MARKETING MEDIA ON OUTPATIENT KNOWLEDGE OF HOSPITALS - Layla Defitria; Panca Radono (Universitas STRADA Indonesia, 2025)
ABSTRACT The background of this research is based on the importance of social media in the dissemination of health information and patient education in the digital era. This study aims to analyze the effectiveness of the use of social media as a marketing tool in increasing patient knowledge about services at Gambiran Hospital, Kediri City. The research method used is quantitative design. Data was collected through questionnaires that were shared with patients before and after they received information through social media posts of Gambiran Hospital.Social media has proven to be effective in increasing patient knowledge about hospital services. The use of social media as a marketing medium has proven to be effective in increasing patient knowledge about outpatient services at Gambiran Hospital, so it is necessary to maintain and always improve the quality and evaluate the program in order to increase patient interaction and involvement, as well as strengthen the image and reputation of the hospital.